PS02.215: DOUBLE STENT INSERTION FOR TRACHEOESOPHAGEAL FISTULA AFTER CHEMORADIOTHERAPY: A CASE REPORT AND REVIEW OF LITERATURE. (14th September 2018) - Nakazato, Hidetsugu; Yoshino, Yutaro; Tomiyama, Takeshi; Nagamine, Shinji; Tomori, Takehiko; Inamine, Susumu; Miyagi, Jun; Nagayoshi, Seiji; Omine, Yasushi; Miyara, Tetsuhiro
Abstract: Background: Tracheoesophageal fistula is a one of the most severe adverse events of chemoradiotherapy (CRT) for esophageal carcinoma. Methods: Case: The patient was an 84-year-old man who was referred to our hospital due to dysphasia, which had persisted for 2 months. Upper gastrointestinal endoscopy demonstrated a semicircular esophageal tumor. Biopsy revealed squamous cell carcinoma. Further examination revealed regional lymph-node metastasis but no distant metastasis. The clinical classification, according to the TNM 7th edition was T4b(trachea)N1M0 Stage IIIC. CRT (using cisplatin (CDDP)/5-fluorouracil (5-FU) infusion with concurrent radiotherapy) was performed. At two weeks after the initiation of CRT, the patient developed pneumonia due to tracheoesophageal fistula. The respiratory infection was controllable and the tumor remained after CRT. Tracheal stent insertion and esophageal stent insertion were performed sequentially as palliative treatments. Results: There were no specific complications in association with stent insertion and the patient was successfully discharged from the hospital. Conclusion: Tracheal and esophageal stent insertion are considered to be safe and feasible palliative treatments for tracheoesophageal fistula. Disclosure: All authors have declared no conflicts of interest.